2015
DOI: 10.1007/s10549-015-3484-2
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines are advantageous, though not essential for improved survival among breast cancer patients

Abstract: The purpose of this retrospective multicenter study was to resolve the pseudo-paradox that the clinical outcome of women affected by breast cancer has improved during the last 20 years irrespective of whether they were treated in accordance with clinical guidelines or not. This retrospective German multicenter study included 9061 patients with primary breast cancer recruited from 1991 to 2009. We formed subgroups for the time intervals 1991-2000 (TI1) and 2001-2009 (TI2). In these subgroups, the risk of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…25 The adherence to the corresponding guide line, specifically to the recommendations on adjuvant endocrine therapy, is high and above 80%. 26 Because aromatase inhibitor treatment is recommended in postmenopausal patients and in lobular breast cancer patients 25 who provide the majority of ESR1-mutated cases in this study, most of the mutated cases have probably been treated with an aromatase inhibitorcontaining regimen.…”
Section: Endocrine Pretreatment Of Metastatic Breast Cancer With Esr1mentioning
confidence: 99%
“…25 The adherence to the corresponding guide line, specifically to the recommendations on adjuvant endocrine therapy, is high and above 80%. 26 Because aromatase inhibitor treatment is recommended in postmenopausal patients and in lobular breast cancer patients 25 who provide the majority of ESR1-mutated cases in this study, most of the mutated cases have probably been treated with an aromatase inhibitorcontaining regimen.…”
Section: Endocrine Pretreatment Of Metastatic Breast Cancer With Esr1mentioning
confidence: 99%
“…Their characteristics and main results are available in Additional files 4 and 5. A direct association between adherence to breast cancer CGs and better overall survival was more frequently observed regardless of the study period [22], the use of different cut-offs or number of deviations to CGs recommendations used to determine adherence [17,42,48] and patient's age [17,18,37,41,44,45]. Although non-adherence was associated with lower survival rate both in triple negative breast cancer (TNBC) and non-TNBC patients, this association was stronger in TNBC than in non-TBNC patients [19,43].…”
Section: Impact On Patient Outcomes Overall Survivalmentioning
confidence: 99%
“…Additionally, this outcome was reported in another 15 studies not meeting the criteria for performing a metaanalysis as specified in the methods section. An association between adherence to breast cancer CGs and better disease-free survival was observed consistently regardless of the study period [22,47], use of different [18,19,38,45] High 0 (0%) - ‡ Percentages exceed 100% because the categories are not mutually exclusive (i.e. some studies involved more than one type of guideline and more than one type of outcome) cut-offs to determine adherence [43,47,48], patient's age [18,41] and subtype of tumour [42,43].…”
Section: Disease-free Survivalmentioning
confidence: 99%
“…We finally included 57 references representing 41 primary studies. Three studies were reported in more than one publication: BRENDA I [12,13,[20][21][22][23][24][25][26][27][28], BRENDA II [29][30][31], and OncoDoc2 [32][33][34]. (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Six studies addressed the overall treatment process (surgery, CT, ET, and RT). These studies represented patients receiving treatment in the period from 1991 to 2009 [28,32,41,48,59,63]. The median adherence was 57.5% (IQR 38.8-67.3%), and ranged from 29 [63] to 91% [32].…”
Section: Overall Treatment Processmentioning
confidence: 99%